OP23 The Iceberg of suicide and self-harm in irish adolescents – a population-based study. (31st August 2015) - McMahon, E; Keeley, H; Cannon, M; Arensman, E; Perry, I; Clarke, M; Chambers, D; Corcoran, P
Abstract : Background: Suicide is a leading cause of death among adolescents, and self-harm is the most important risk factor for suicide. The "iceberg" of suicidal behaviour has been postulated, in which the tip of the iceberg is the highly visible but rare event of suicide, beneath this higher rates of hospital-treated self-harm, and at the base the very common but often hidden phenomenon of self-harm which does not come to the attention of health services. The relative incidence of each of these behaviours has not previously been reliably established for any population. The purpose of this study was to establish the relative incidence of adolescent suicide, hospital-treated self-harm and self-harm in the community. Methods: Annual suicide rates were calculated for 15–17 year-olds in the Cork and Kerry region in Ireland based on data from the Central Statistics Office. Rates of hospital-treated self-harm in this region were calculated based on data from the Irish National Registry of Deliberate Self-Harm. Rates of self-harm in the community were assessed using a school-based survey of 3, 881 adolescents in the Cork and Kerry region, the Child and Adolescent Self-harm in Europe (CASE) study. Results: The annual suicide rate was 10/100, 000 (95% CI: 0–22.39). Suicide was six times more common among boys than girls. The annual incidence rate of hospital-treated self-harm was approximately 344/100, 000 (95% CI: 271.67–417.16), with the female rate almost twice the male rate. The rate of self-harm in the community was 5, 700/100, 000 (95% CI: 4893.28–6436.77), and girls were almost four times more likely to report self-harm. For every boy who died by suicide, 16 presented to hospital with self-harm and 146 reported self-harm in the community. For every female suicide, 162 girls presented to hospital with self-harm and 3, 296 reported self-harm. Conclusion: Gender differences in relative rates of self-harm and suicide are very large. The relative incidence of suicide and self-harm among boys (one suicide to 146 with self-harm in the community) indicates that boys who have harmed themselves may be at particularly high risk of suicide. Knowledge of the relative incidence of self-harm and suicide in adolescents can inform prevention programmes and services.